2016
DOI: 10.1111/ced.12852
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of T cells in early evolving segmental vitiligo

Abstract: Recent studies have suggested an overlapping autoimmune mechanism between segmental vitiligo (SV) and nonsegmental vitiligo (NSV). Although T-cell infiltration is observed in the margins of active lesions in NSV, the histopathological characteristics of the active margin of SV are not well known. To determine if T-cell inflammatory responses are present in the active margin of SV lesions, biopsies were taken from the active margin of a lesion in 12 patients with early or actively spreading SV and compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In a relatively small study, immunohistochemistry revealed a lesional lymphocytic infiltrate in 8/12 of progressing SV patients comparable to NSV with a predominance of CD8 + T cells migrating toward the basal layer. A non-significant increase in IFN-g was observed (23). In a larger study (SV n = 50), histopathological inflammatory features were noticed in 78% (38/50) of patients.…”
Section: Auto-immunity In Segmental Vitiligomentioning
confidence: 79%
“…In a relatively small study, immunohistochemistry revealed a lesional lymphocytic infiltrate in 8/12 of progressing SV patients comparable to NSV with a predominance of CD8 + T cells migrating toward the basal layer. A non-significant increase in IFN-g was observed (23). In a larger study (SV n = 50), histopathological inflammatory features were noticed in 78% (38/50) of patients.…”
Section: Auto-immunity In Segmental Vitiligomentioning
confidence: 79%
“…• Mutated melanocytes are possible targets in genetically determined mosaic patterns in segmental vitiligo (SV) or some cases of nonsegmental vitiligo (NSV). This is leading to one attack of permanent and localized depigmentation early in life [30].…”
Section: How Do the Lymphocytes Attack The Melanocytes?mentioning
confidence: 99%
“…Only recently, immunemediated pathophysiology of SV has been recognized. Increasing evidence has shown immune-based cytotoxic destruction of melanocytes in SV, with lesional IFN-γ-producing melanocyte-antigen reactive CD8 + T cell infiltrates migrating to the basal layer (Attili and Attili, 2013, Shin et al, 2016, van Geel et al, 2010. Although NSV is closely associated with other autoimmune disorders, e.g.…”
Section: Introductionmentioning
confidence: 99%